Point beauty contest: measuring the distribution of focal points on the individual level - Schmidt, Robert J. (Discussion paper series, 2019)
We propose the Point Beauty Contest, a mechanism to identify the distribution of focal points on the individual level. By contrast to conventional coordination, subjects coordinate by the distribution of points. This allows for nuanced coordination strategies, as subjects can invest in multiple alternatives at the same time and weigh their choice. A subject's strategy choice then reveals her perception of the distribution of focal points. In an experiment on the elicitation of social norms, we compare the mechanism with conventional coordination. The data confirms the theoretical predictions regarding coordination behavior and demonstrates that the proposed technique is suited to identify the distribution of focal points on the individual level. Using Monte Carlo simulations, we find that the proposed mechanism identifies focal points on the population level more efficiently than conventional coordination. We point to the possibility of using the mechanism as a simple method to directly measure strategic uncertainty.
Keywords: Arbeitspapier; Graue Literatur